RANCANG BANGUN APLIKASI PENGINGAT MAKAN DAN MINUM BERBASIS ANDROID - Taftazani Ghazi Pratama; Hermawan Abdillah Hamka; Fida Maisa Hana (LPPM Unbaja, 2024)
Eating and drinking are basic daily human needs which are used in various activities from waking up to going back to sleep. A person's activities can be carried out well if he regulates regular eating and drinking patterns. On the other hand, someone who does not have a regular eating and drinking pattern will cause the emergence of various diseases, one of which is gastritis. Therefore, we need a solution to improve eating and drinking patterns so that the body remains healthy and avoids various diseases. The methodology used to design this application is the ADDIE method. This research aims to design an Android-based eating and drinking reminder application. The application that has been built can make it easier for someone to manage their daily eating and drinking patterns and remind them of their daily eating and drinking consumption schedule by sending notifications to the user's smartphone.